Expanding the phenotype of BICD2 mutations toward skeletal muscle involvement. (22nd November 2016) - Unger, Andreas; Dekomien, Gabriele; Güttsches, Anne; Dreps, Thomas; Kley, Rudolf; Tegenthoff, Martin; Ferbert, Andreas; Weis, Joachim; Heyer, Christoph; Linke, Wolfgang A.; Martinez-Carrera, Lilian; Storbeck, Markus; et al.
Abstract : Objective: To expand the spectrum of bicaudal D, Drosophila, homologue 2 ( BICD2 ) gene – related diseases, which so far includes autosomal dominant spinal muscular atrophy with lower extremity predominance 2 and hereditary spastic paraplegia due to mutations in the BICD2 gene. Methods: We analyzed 2 independent German families with clinical, genetic, and muscle MRI studies. In both index patients, muscle histopathologic studies were performed. Transfection studies were carried out to analyze the functional consequences of the disease-causing mutations. Results: We identified the mutations p.Ser107Leu and p.Thr703Met in the BICD2 gene in the 2 families, respectively. In contrast to other patients carrying the same mutations, our patients present features of a myopathy with slow progression. Immunofluorescence studies and immunoelectron microscopy showed striking impairment of Golgi integrity, vesicle pathology, and abnormal BICD2 accumulation either within the nuclei (p.Ser107Leu) or in the perinuclear region (p.Thr703Met). Transfection studies confirmed BICD2 aggregation in different subcellular locations. Conclusions: Our findings extend the phenotypic spectrum of BICD2 -associated disorders by features of a chronic myopathy and show a pathomechanism of BICD2 defects in skeletal muscle.